2016
DOI: 10.1186/s12864-016-3199-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel targets of diabetic nephropathy and PEDF peptide treatment using RNA-seq

Abstract: BackgroundDiabetic nephropathy (DN) is a major complication of type1 and type 2 diabetes. Understanding how diabetes regulate transcriptome dynamics in DN is important for understanding the biology of the disease and for guiding development of new treatments.ResultsWe analyzed the kidney transcriptome of a DN mouse model, D2.B6-Ins2 Akita/MatbJ, before/after treatment with P78-PEDF. Age, weight, and gender-matched mice and wild-type (wt) littermates were treated at 6 weeks (early treatment) or 12 weeks (late t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
(63 reference statements)
2
16
1
1
Order By: Relevance
“…We also found that the absence of Mcpt6 was associated with elevated expression of the micro RNA miR3098. Interestingly, miR3098 has previously been implicated in lung cancer (Wang, Xu, & Wang, ) and diabetes (Rubin, Salzberg, Imamura, Grivitishvilli, & Tombran‐Tink, ), although the exact role miR3098 under these conditions has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the absence of Mcpt6 was associated with elevated expression of the micro RNA miR3098. Interestingly, miR3098 has previously been implicated in lung cancer (Wang, Xu, & Wang, ) and diabetes (Rubin, Salzberg, Imamura, Grivitishvilli, & Tombran‐Tink, ), although the exact role miR3098 under these conditions has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between lncRNA-AI838599 and kidney is also reported previously. GSE87899 (GEO DataSets) [33] showed increased lncRNA-AI838599 expression in the kidney of D2.B6-Ins2 Akita /MatbJ DN mouse model compared to the wild type. e similar expression trend of lncRNA-AI838599 was also seen in miR-25 knockdown mice that show similar phenotypes of DN such as proteinuria, extracellular matrix accumulation, and podocyte foot process effacement [34].…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression data were provided as supplementary material. The heat map of gene differentiation was generated using the method described by Rubin et al [ 21 ]. Briefly, a heat map of the median-centered FPKM (fragments per kilobase of exon per million fragments mapped) values corresponding to the transcripts in samples was generated using the heatmap.2 function of the gplots R package.…”
Section: Methodsmentioning
confidence: 99%